2021
DOI: 10.3390/ijms22179194
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Prediction of Gas Chromatographic Retention Indices for a Wide Variety of Polar and Mid-Polar Liquid Stationary Phases

Abstract: Prediction of gas chromatographic retention indices based on compound structure is an important task for analytical chemistry. The predicted retention indices can be used as a reference in a mass spectrometry library search despite the fact that their accuracy is worse in comparison with the experimental reference ones. In the last few years, deep learning was applied for this task. The use of deep learning drastically improved the accuracy of retention index prediction for non-polar stationary phases. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…It can be concluded that the 1D CNN gives an appropriate accuracy for the prediction of CCS values for peptides and can be used instead of the RNN or together with the RNN as part of an ensemble of models. An ensemble of independent models is usually more accurate than each of the models [ 19 , 20 , 23 ]. The averaging of the results of various models improves the accuracy [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the 1D CNN gives an appropriate accuracy for the prediction of CCS values for peptides and can be used instead of the RNN or together with the RNN as part of an ensemble of models. An ensemble of independent models is usually more accurate than each of the models [ 19 , 20 , 23 ]. The averaging of the results of various models improves the accuracy [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…An ensemble of independent models is usually more accurate than each of the models [ 19 , 20 , 23 ]. The averaging of the results of various models improves the accuracy [ 20 ]. Figure 3 demonstrates a correlation between the predicted and reference values and error distributions for different charge states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In criterion (vi), a larger threshold value is used compared with criterion (i): 100 units instead of 70. This is related to the lower accuracy of the RI prediction for the polar stationary phases, compared with the prediction for the non-polar stationary phases [30]. The previously published model [30] was used for prediction.…”
Section: Workflow For Non-target Analysismentioning
confidence: 99%
“…Stein et al used group additivity to estimate the RI values of diverse compounds passed through polar and nonpolar columns with mean absolute prediction errors of 46 and 65, respectively. The use of deep learning methods for improving upon QSAR has been a topic of investigation since the start of the deep learning revolution and has grown to encompass a large number of methods. , A number of these deep learning QSAR methods have been used to predict RI values , from the molecular structure with varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%